Synthesis of stable anisotropic carbon particle aggregates covered by surface nano-graphitic sheets. (July 2015) - Mukawa, Kei; Oyama, Naganobu; Ando, Hiroaki; Sugiyama, Takashi; Ogo, Shuhei; Sekine, Yasushi
Abstract: For this study, pyrolytic carbon particles were synthesized in a pyrolytic reactor in which a moderate electric field by DC power was generated between two electrodes at the center of the pyrolysis zone at 1573 K. The resulting carbon particles, which were collected on the top of the electrode, were analyzed to assess their microstructure and nanostructure using TEM observation, Raman spectroscopy, X-ray diffraction measurement, and light scattering size distribution measurements. Results showed that the resulting carbon particles formed a characteristic structure; the anisotropic chain-like configuration (fractal dimension, Df  = 1.65 ± 0.02), with graphitic thin nanolayers having high crystallinity covering the surface of these aggregates. Morphological analysis with the concept of the fractal dimension of the aggregate indicates that the electric field regulates the aggregate morphology. The other experiment which the carbon source was fed onto prefabricated pyrolysis carbon particles under 1537 K showed that surface graphitic layers on the aggregate was derived from gas phase carbon sources, not from graphitizing of the surface structure of carbon particles. The ultrasonication of carbon particles with/without surface graphitic layers in the ethanol solution also confirmed that the specific role of the layers that supports stabilization of the aggregate configuration.